Comparison of Hearing Result and Graft Uptake Rate between Temporalis Fascia and Tragal Cartilage in Endoscopic Myringoplasty - Shrestha, B. L.; Shakya, S.; Pradhan, A.; Dhakal, A.; KC, A. K.; Shrestha, K. S.; Pokharel, M. (Kathmandu University Medical Journal, 2022)
Background There are different methods to repair the perforation of the tympanic membrane. Recently cartilage has been used for the repair and results are comparable to temporalis fascia. For surgical procedure endoscope had added good assistance in middle ear surgery. Though the one hand technique the image quality and results are on par with the use of a microscope. Objective To compare the graft uptake rate and hearing results between temporalis fascia and tragal cartilage in endoscopic myringoplasty. Method This is a prospective, longitudinal study conducted among 50 patients who underwent endoscopic myringoplasty using temporalis fascia and tragal cartilage with 25 patients in each group. The hearing was assessed by comparing pre with post-operative ABG (Air bone gap) and ABG closure in speech frequencies (500Hz, 1 KHz, 2 KHz, 4 KHz). The status of graft and hearing results was evaluated on 6 months of follow up in both the groups. Result Out of total 25 patients enrolled for study in both (temporalis fascia and cartilage) groups, 23 (92%) patients in each group had graft uptaken. The audiological gain in the temporalis fascia group was 11.37±0.32 dB whereas in the tragal cartilage group it was 14.56±1.22dB. The audiological gain between the two groups did not show any statistically significant (p = 0.765). However, the pre and post-operative hearing difference was statistically significant in both temporalis fascia and tragal cartilage group. Conclusion Tragal cartilage has similar graft uptake rate and hearing gain when compared with temporalis fascia in endoscopic myringoplasty. Hence, tragal cartilage can be used for myringoplasty whenever required without any fear of deterioration in hearing.